Chemical solution-derived SrMg2(PO4)2:Eu2+ blue phosphor for ultraviolet emitting diodes - Hwang, Kyu-Seog; Hwangbo, Seung; Kim, Jin-Tae (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
Eu2+-doped SrMg2(PO4)2 phosphor with blue emission was prepared by the low temperature chemical solution process using inorganic salts as a starting material. Transparent sol was preheated at 300 °C for 120 min and then precursor was finally annealed at 900 °C for 240 min in a reducing CO atmosphere. Crystallinity, surface morphology and luminescent properties have been investigated. The phosphor emits bright blue luminescence with a peak wavelength at 423 nm under near-ultraviolet excitation at 363 nm.
Optica Applicata, Vol. 40, 2010, nr 4, s. 943-948
Keywords: sol-gel; optyka; SrMg2(PO4)2; phosphor; blue